2015
DOI: 10.3390/w7010202
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Demand Dynamics of Residential Water End-Uses

Abstract: Water demand prediction by end-use at an appropriate spatial and temporal resolution is essential for planning water supply systems that will supply water from a diversified set of sources on a fit-for-purpose basis. Understanding seasonal, daily and sub-daily water demand including peak demand by end-uses is an essential planning requirement to implement a fit-for-purpose water supply strategy. Studies in the literature assume that all indoor water uses except evaporative cooler water use are weather independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 11 publications
3
38
0
4
Order By: Relevance
“…No significant seasonal trend of the water demands was observed for the field data examined, contrary to what happens for residential users in some countries [24,25].…”
Section: The Monitoring Systems and The Data Samplesmentioning
confidence: 76%
“…No significant seasonal trend of the water demands was observed for the field data examined, contrary to what happens for residential users in some countries [24,25].…”
Section: The Monitoring Systems and The Data Samplesmentioning
confidence: 76%
“…Currently, the seasonal demand dynamics as, for example, discussed in [26], are only taken into account in a simplified way. A peak day demand is used for network design, an average day with a diurnal demand pattern is used to assess the impact of the decentralised measures and an assumed low consumption day being one third of the average daily demand is used for water quality assessments in the potable water supply network.…”
Section: Hybrid Water Supply Estimation With Urbanbeatsmentioning
confidence: 99%
“…What is required for planning decentralized systems is a much finer understanding of temporal and spatial demand variability at end‐use level. Rathanayaka et al provide a comprehensive review of the existing models to predict end‐use water demand and approaches to arrive at their estimation . In another study, authors identified the factors affecting spatial and temporal variability in water demand and developed a new stochastic–deterministic approach to predicting water demand .…”
Section: Dimensions Of Hwsmentioning
confidence: 99%
“…Rathanayaka et al provide a comprehensive review of the existing models to predict end‐use water demand and approaches to arrive at their estimation . In another study, authors identified the factors affecting spatial and temporal variability in water demand and developed a new stochastic–deterministic approach to predicting water demand . This level of modeling scale is critical in assisting to determine the optimal design scale for decentralized water supply systems.…”
Section: Dimensions Of Hwsmentioning
confidence: 99%